Implementing (un)fair procedures? Favoritism and process fairness when inequality is inevitable - Robert J. Schmidt; Stefan T. Trautmann (University of Heidelberg, Department of Economics, 2019)
We study allocation behavior when outcome inequality is inevitable but a fair process is feasible, as in selecting one person from several candidates for a job or award. We show that allocators may be influenced by inappropriate criteria, impeding the implementation of a fair process. We study four interventions to induce process fairness without restricting the allocator's decisions: Increasing the transparency of the allocation process; providing a private randomization device; allowing the allocator to delegate to a public randomization device; and allowing the allocator to avoid information on inappropriate criteria. All interventions except transparency have positive effects, but differ substantially in their impact.
Keywords: D63; D73; J70; 330; equality; procedural justice; discrimination